Domestic Competition, Cyclical Fluctuations, and Long-Run Growth in Hong Kong Sar - Zitzewitz, Eric (IMF Working Papers; Working Paper ;, 2000)
This paper provides an empirical assessment of the degree of competition in Hong Kong SAR using industry-level data. Although due to data limitations only approximate measures of competitiveness can be estimated, the results do suggest that Hong Kong SAR is as competitive as a typical OECD economy. The dramatic shift of the economy toward services over the last decade has also made it slightly less competitive on average. Imperfect competition is not leading to counter-cyclical markups and slower price adjustment as some theories predict, however, since markups are more pro-cyclical than in OECD countries. Lastly, markups are sufficiently imperfectly competitive in both Hong Kong SAR and the OECD to significantly downwardly bias growth accounting estimates of total factor productivity in Asian NICs vis-a-vis OECD countries.